A new adventive parthenogenetic Nocticola species (Blattodea: Nocticolidae) found in Florida, USA and Vienna, Austria - Wang, Junkai; Jeon, Alan; Cognato, Anthony I. (Zootaxa, 2025)
Nocticolidae cockroaches are primarily distributed in tropical Africa, South and Southeast Asia, and Australia. Three females of an unidentified nocticolid species were collected in Florida, USA, which is the first record of this family in the New World. Morphological and molecular data (COI and 16S) confirmed their identity as a Nocticola species which also occurs in the US pet trade and as a greenhouse population in Austria. Phylogenetic evidence supported its identification as an undescribed species that is a likely adventive from Southeast Asia. Nocticola vagus sp. nov. was described based on diagnostic morphology and DNA sequences. In addition, the new species is parthenogenetic which is the first record for Nocticolidae. This trait and human-mediated dispersal likely facilitated its establishment across the globe.